Collateral damage in education: implications for the time of COVID-19. Issue 1 (2nd January 2023) - Saito, Eisuke
ABSTRACT: The Coronavirus disease of 2019 (COVID-19) has impacted the world immensely in terms of both global health and economy. It has exacerbated the gap between the economically advantaged and disadvantaged groups in terms of access to various resources and opportunities across the world. This situation has been described as ' collateral damage ', which represents unexpected and unintended negative impacts that deprive the poor of certain opportunities and rights. Interestingly, the differences in capability to respond to the issues caused by COVID-19 are observed in developed and developing countries alike. This paper aims to discuss the potential risk factors that encourage students to drop out as collateral damage due to COVID-19, based on the literature on developing South East Asian countries. This commentary argues that collateral damage caused by COVID-19 has revealed a serious limitation in the nature of formal schooling in South East Asia. Although more socio-economically vulnerable groups can participate in formal schooling, there is still not a sufficiently communal climate in these schools that would prevent them from dropping out.